Spymaster's prism : the fight against Russian aggression - Devine, Jack, 1940- (Lincoln : Potomac Books, An imprint of the University of Nebraska Press, 2021)
In Spymaster's Prism, the legendary former spymaster Jack Devine aims to ignite public discourse on our country's intelligence and counterintelligence posture against Russia, among other adversaries.
Appendix: Russia's Known Elicitation Attempts in Trump's Inner Circle -- Notes -- Bibliography -- Index
eBooks on EBSCOhost
Keywords: United States. -- Department of State -- Security measures; United States. -- Department of State; United States. -- Central Intelligence Agency; Espionage, American -- Russia (Federation); Espionage, Russian -- United States; Cyberterrorism -- Russia (Federation); United States -- Foreign relations -- Russia (Federation); Russia (Federation) -- Foreign relations -- United States; Espionnage américain -- Russie; Espionnage russe -- États-Unis.; Cyberterrorisme -- Russie; États-Unis -- Relations extérieures -- Russie; Russia & the Former Soviet Union; Europe; HISTORY; United States; Intelligence & Espionage; POLITICAL SCIENCE; Security systems; Espionage, Russian; Espionage, American; Diplomatic relations; Cyberterrorism; United States; Russia (Federation)